ANALISIS RASIO PROFITABILITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP FINANCIAL DISTREES PADA PT JAYA KONTRUKSI MANGGALA PRATAMA TBK - Ainun Fadilah; M Rimawan (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
The investors who invest will be aware of and ensure the condition of the company whether it is experiencing financial distrees or the company is in good condition. Therefore, it is necessary to conduct a financial analysis of the company by looking at its financial ratios. This study aims to examine the independent variables in the form of Profitability Ratios, Liquidity Ratios and Solvency Ratios to Financial Distrees as the dependent variable. This research was conducted on the construction sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2011-2020 with a population of 20 years. The sampling technique in this study used purposive sampling which resulted in a sample of 10 years. The analytical method used in this study is the classical assumption test, multiple linear regression analysis and hypothesis testing used SPSS V.21. The results showed that partially the Profitability Ratio variable had a significant effect on financial difficulties, Liquidity and Solvency Ratio variables had no significant effect on financial difficulties. Simultaneously, Profitability Ratio, Liquidity Ratio and Solvency Ratio have a significant effect on financial distrees.